Organizational aspects of providing medical care to children with injuries at the regional level - Z. V. Lashkul; V. V. Chemirisov; V. L. Kurochka; N. Y. Motovytsya; L. D. Yarova (Сучасні медичні технології)
Purpose of the study. To study and analyze the trend of injuries among children aged 0-14 years and organizational aspects of providing them with medical care at the regional level.